Analysis of optimization on fund disbursement order monitoring system in the treasury based on the regional development information system: Case study of the local government finance and asset office of Bojonegoro Regency - Umi Fatimatur Rosyidah; Hanifah Zuniatin; Frida Fanani Rohma (Journal of Applied Sciences in Accounting, Finance, and Tax, 2024)
The Regional Development Information System (SIPD) is designed by the government to make it easier for stakeholders to input and manage regional finances. However, not all local governments are able to develop along with increasingly massive technological developments. The Bojonegoro government, with quite a lot of sources of income dominated by the oil and gas sector, is quite adaptive in implementing the Regional Development Information System (SIPD). Thus, this research seeks to investigate optimizing the fund disbursement order monitoring system in the treasury based on the regional development information system in Bojonegoro. This research employed qualitative methods, where researchers used data collection techniques by means of observation, interviews and documentation. The object of this research is the Local Government Finance and Asset Office (BPKAD) of Bojonegoro Regency, especially in the treasury sector and the subject of this research is the Regional Development Information System (SIPD). The research findings indicate that SIPD has a crucial role in realizing transparent and reliable financial management, making it easier to supervise. However, achieving transparency and monitoring efficiency can only be supported by an implementation process that has been carried out in an integrated manner. Regional government synergy has a crucial role to play in encouraging the process of unifying all regional development information systems and regional information systems in order to accelerate the implementation of SIPD.